Multiple Tendons Variations were Observed in a Male Old Cadaver - Ahmed Abdelmotal, Dr. Mohammed Abdelsalam (مجلة الجزيرة للعلوم الصحية; مجلد 15 عدد 1 (2019), 2019)
Background: Anatomical variations and arrangements of muscles have great importance in many clinical and surgical procedures. Objectives: To record any anatomical variation during the complete dissection of a 75 years old male cadaver. Methods: Complete dissection of a preserved embalmed male cadaver about 75 years old under guide of Cunnigham’s Manual of Practical Anatomy for academic year 2018-2019 undergraduate students, at the department of human anatomy at Napata College. Result: Many anatomical variations were recorded during the dissection. There was agenesis of palmaris longus muscles in both sides, the abductors pollicis longus muscles, extensor digiti minimi muscles were presented with two tendons in both sides. Extensor digtorum tendons on the right side was doubled to the ring finger, there was no independent tendon to the little finger, the lateral tendon of the ring finger gave off intertendinous connection to the lateral tendon of extensor digiti minimi. Extensor digtorum tendons on the left side had four tendons the tendon for little finger was divided into two slips joining the ring tendon and medial tendon of extensor digit minimi. Moreover intertendinous connection of the extensor digitorum tendons in both sides was seen, between the little and ring fingers tendons of the left side while the medial tendon of the ring finger provided an intertendinous connection to middle finger on the right side. Conclusion: Awareness of these anatomical variations has a significant importance in academic and clinical practice.